Pancasila Values in Indonesian Higher Education Life: ‎Perspectives on Education, Socio Culture, and Digital ‎Transformation - Angraini, Peggy Dian Septi Nur; Wardana, Rafiq Adi (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to comparatively examine how Pancasila values are implemented across educational, socio-cultural, and digital-transformation dimensions at Sebelas Maret University, Muhammadiyah University of Surakarta, and Sragen University, and to identify common patterns and institution-specific mechanisms. A descriptive qualitative, comparative multiple-case design combined normative legal and empirical approaches. Informants were purposively selected from university leaders, faculty members, educational staff, and student representatives. Data were obtained through document analysis, non-participant observation, semi-structured interviews, and focus group discussions, then analyzed thematically using deductive and inductive interpretation, with credibility strengthened through triangulation and member checking. The findings show that all three universities integrate Pancasila into curricula, student activities, institutional culture, community engagement, and digital initiatives, but with different emphases. Sebelas Maret University prioritizes research, policy development, multicultural facilities, and PSPP; Muhammadiyah University of Surakarta emphasizes the integration of Islamic, social, and national values through PSBPS; and Sragen University relies more strongly on local wisdom, community-based learning, mutual cooperation, and community service. Digital transformation across the cases also involves digital literacy, ethics, and responsible citizenship rather than technology alone. These findings indicate that Pancasila implementation is adaptive to institutional identity while maintaining common normative objectives. The study is limited to three universities and primarily institutional perspectives; therefore, future research should involve broader samples and measurable indicators of student outcomes, digital ethics literacy, and inter-university.